HASIL BELAJAR EKONOMI MODEL PROBLEM POSING DAN DISKUSI KELOMPOK MEMPERHATIKAN KEMAMPUAN AWAL - Rika Tria Ananda; Tedi Rusman; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2015)
The research was motivated by the lack of economic learning outcome. The aim of research was to determine the differences between economic learning outcome and the interaction of learning model and initial ability. The method used was the method of comparative experimental approach. The research population was 157 students with a sample of 58 students. Results of analysis showed that (1) there were differences in learning outcomes of economics students using Problem Posing model compared to group discussion, (2) the results of economics learning at the student who has low initial ability using Problem Posing model was lower than students who were using the Group Discussion , (3) The economics students have high initial ability using Problem Posing model was higher than students who were using the Group Discussion, (4) there was an interaction between the models with the initial ability on economic subjects. (5) there was a difference between high and low initial ability of the results of the economic study.Penelitian dilatarbelakangi oleh rendahnya hasil belajar ekonomi. Tujuan penelitian untuk mengetahui perbedaan hasil belajar ekonomi serta interaksi model pembelajaran dan Kemampuan Awal. Metode yang digunakan adalah metode komparatif pendekatan eksperimen. Populasi penelitian ini 157 siswa dengan jumlah sampel 58 siswa. Hasil analisis (1) terdapat perbedaan hasil belajar ekonomi siswa menggunakan model Problem Posing dibandingkan menggunakan Diskusi Kelompok, (2) hasil belajar ekonomi pada siswa memiliki kemampuan awal rendah menggunakan model Problem Posing lebih rendah dibandingkan dengan siswa menggunakan Diskusi Kelompok., (3) hasil belajar ekonomi siswa memiliki kemampuan awal tinggi menggunakan model Problem Posing lebih tinggi dibandingkan siswa menggunakan Diskusi Kelompok., (4)ada interaksi antara model dengan kemampuan awal pada mata pelajaran ekonomi. (5) ada perbedaan antara kemampuan awal tinggi dan rendah terhadap hasil belajar ekonomi.Kata kunci: diskusi kelompok, hasil belajar ekonomi, kemampuan awal siswa, problem posing.